Prospects For the Implementation of Cloud Radio Access Network of Cellular Networks - Sotvoldiev Said-Akbarxon Shukurjon o’g’li (Zien Journals, 2021)
Today, many mobile operators are facing a number of challenges in expanding their Radio Access network infrastructure due to rapid technology upgrades and rising device prices. For operators, it is important that expand of their radio access network in order to meet the needs of users, improve network coverage, and reduce network overloading. Cloud RAN architecture is considering as a priority direction of development of radio access network of next generation cellular networks. This article focused on prospects of implementing Cloud RAN.
Keywords: Radio Access Network; Remote Radio Unit/Head; Base Band Unit; virtual Base Band Unit Pool